2010
DOI: 10.1016/j.bmc.2010.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prolyl oligopeptidase with a synthetic unnatural dipeptide

Abstract: The synthesis of a new inhibitor of prolyl oligopeptidase, containing a piperidine ring, together with an X-ray structure of its complex with the enzyme, is described. This provides evidence that covalent inhibitors of POP do not have to be limited to structures containing 5-membered N-containing heterocyclic rings. inhibitor:Leave this area blank for abstract info. Abstract-A new inhibitor, containing a linked proline-piperidine structure, for the enzyme prolyl oligopeptidase (POP) has been synthesised and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(30 reference statements)
0
6
1
Order By: Relevance
“…We have previously found that substituting the five-membered ring with a six-membered ring was detrimental to the inhibitor’s activity (Figure ) . This contrasted with the finding from Racys and co-workers who reported a very active inhibitor built around a piperidine ring . In the present work, the substitution of the pyrrolidine ring of 8 by a piperidine ring ( 9 ) led to a decrease of inhibitory activity.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…We have previously found that substituting the five-membered ring with a six-membered ring was detrimental to the inhibitor’s activity (Figure ) . This contrasted with the finding from Racys and co-workers who reported a very active inhibitor built around a piperidine ring . In the present work, the substitution of the pyrrolidine ring of 8 by a piperidine ring ( 9 ) led to a decrease of inhibitory activity.…”
Section: Resultscontrasting
confidence: 98%
“…22 This contrasted with the finding from Racys and co-workers who reported a very active inhibitor built around a piperidine ring. 39 In the present work, the substitution of the pyrrolidine ring of 8 by a piperidine ring (9) led to a decrease of inhibitory activity.…”
Section: ■ Results and Discussionmentioning
confidence: 50%
“…The selection of R 1 and R 2 groups considered the synthetic feasibility. Figure a shows the binding mode of Cbz-Pro-Pip-CN cocrystallized with POP . As with other cocrystallized ligands, this structure revealed two key hydrogen bonds with Arg643 and Trp595, a covalent bond with Ser554 and hydrophobic interactions with Phe173.…”
Section: Resultsmentioning
confidence: 83%
“…Figure 5a shows the binding mode of Cbz-Pro-Pip-CN cocrystallized with POP. 29 As with other cocrystallized ligands, this structure revealed two key hydrogen bonds with Arg643 and Trp595, a covalent bond with Ser554 and hydrophobic interactions with Phe173. Our compounds were docked and compared to this ligand cocrystallized structure (Figure 5b−f).…”
Section: ■ Introductionmentioning
confidence: 66%
“…the removal of oxalate group and replacement of diethyl amine with acetate group. The structure was designed using structure sketching utility by PubChem [62]. Later on, it was docked with PC-POP, as shown in Figure 11.…”
mentioning
confidence: 99%